PEAT FOREST HEALTH ANALYSIS ON LANDSAT 8 OLI / TIRS IMAGERY USING NDVI METHOD IN KOTAWARINGIN TIMUR REGENCY - Rois Saida Sanjaya; Mitha Fitria Anggraini; Mahendra Zhafir Pratama (Faculty of Social and Political Sciences Universitas Kristen Indonesia, 2020)
The degradation of peatland ecosystem has been a mayor impact on the local environment as well as its surroundings such as fires, irriversible drying and dome collapse. This paper presents the application of satellite remote sensing dan GIS techniques to detect and identify peat forest healt in Kotawaringin Timur, Cental Kalimantan Province, Indonesia. Mapping the spasial distribution of peat forest healt is important for making in land management and mitigation of peatland forest fires. This study uses the integration beetwen GIS software and Landsat 8 OLI/TIRS satellite data to identify peatland healt using NDVI in Kotawaringin Timur Regency. This area were picked up as pilot project area for this research because these areas historically had many fire spots on last few years. The result data processing of landsat 8 satellite image shows that 116586,4 hectares of Kotawaringin Timur area is disturbed peatland. Base on the result of landsat 8 image processing data can be seen some areas of Kotawaringin Timur indicate green color means the peat area, and the health level of the peat forest in Kotawaringin Timur Regency is already in the damaged category. Keywords: Peat forest healt, NDVI, GIS, Landsat 8